Groundwater Conservation Model in Coastal Plain of Semarang City - Setyawan Purnama; Andri Kurniawan; Sudaryatno Sudaryatno (Forum Geografi, 2006)
There are three objectives of this research. First, to build the model of groundwater usage and conservation in the research area. Second, to identify the behaviour of model in various usages and conservations. Third, to formulate the policy of groundwater resources management that suitable with the region caracteristic. As a result, show that the programme Powersim 2.5c can be used dan applied in hydrologis, especially in building groundwater conservation model. The conservation model that significantly suitable are to decrease the usage of water in domestic and industrial sector. Relationship by the third objectives, the some policies that can be carried out to conservations, namely decreasing water usage, restricting industrial growth, restricting settlement growth (especially in recharge area) and increasing the capacity of PDAM production.